Perbedaan Kelelahan Kerja Akibat Paparan Getaran mekanis pada operator weaving dan spinning di pt. Kusumahadi Santosa Karanganyar - Sumodiharjo, Sumodiharjo, dr. Bapak Hardjanto, .,MS,Sp.Ok, Dwi Astuti, SKM., M.Kes (2016)
PT. Kusumahadi Santosa is a textile company that utilizes tools that cause vibration of high intensity based on the results of a survey in which 7 out of 10 workers, especially in the weaving and at the spinning experiencing fatigue caused by mechanical vibration which is indicated by several complaints by workers at rest. The purpose of this study was to determine whether there are differences in fatigue due to mechanical vibration to the operator weaving and spinning in PT. Kusumahadi Santosa Karanganyar. This type of research is observational analytic using cross sectional approach. The population in this study as many as 95 people a part of weaving and spinning sections 83 people so the sample results based on inclusion criteria where the weaving and spinning as much as 80. The analysis used was Wilcoxon test showed no difference in fatigue due to mechanical vibration to the operator weaving and spinning in PT , Kusumahadi Santosa Karanganyar with a significance value of 0.012 <0.05 in the weaving and 0,001 <0.05 in the spinning. Based on the measurement results section of spinning his fatigue level higher than the spinning section. Suggested there should be oversight of the company supervisor to discipline the use of personal protective equipment properly, regular monitoring, carried out special medical examinations at least twice a year workers